Printmaking – new and old technologies – a conversation - Coldwell, Paul; Laidler, Paul (PORTO ARTE: Revista de Artes Visuais, 2013)
This paper, through a conversation between Professor Coldwell and Dr Laidler, considers the ongoing relationship between old and new technologies within fine art printmaking. In particular it explores how ideas move between virtual and real, and the need for printmakers to engage with physical objects. As case studies both authors reflect on the making of particular works, Laidler’s Laser engraving "Murmurs from Earth" and Coldwell’s laser cut relief prints "Lines and Branches".